Optimization of Red Ginger, Alginate and Drying Time on the Characteristics of Antidiabetic Effervescent Powder Drink with Combination Design - Muhammad Fajri Romadhan; Rahmawati Rahmawati; Wardina Humayrah; Femi Fahturohmah (Food ScienTech Journal, 2025)
Red ginger and alginate contain antidiabetic compounds such as flavonoids. The purpose of this study was the optimization of red ginger, alginate, and drying time on the characteristics of antidiabetic effervescent powder drinks with a combined design. The tests were physical quality (flow time, dissolving time, angle of repose, and total soluble solids) and chemical quality (water content, antioxidant activity, total sugar, and pH value). Data were analyzed with ANOVA on Design Expert 13®. The optimal formulation consists of a red ginger concentration of 6.497%, alginate at 1.007%, and a drying time of 1.987 hours. The resulting product exhibited a repose angle of 37.89°, dissolution time of 75.65 seconds, bulk density of 0.58 g/mL, total soluble solids at 2.4°Brix, flow time of 0.8 seconds, moisture content of 4.75%, pH of 5.1, antioxidant activity (IC50) of 172.79 ppm (classified as weak), and total sugar content of 29.59%.